The Effectiveness of Limited Dynamic Wrist Splints on the Symptoms, Function, and Strength of Women with Carpal Tunnel Syndrome: A Controlled Trial Study - seyedeh marjan jaladat; mehdi abdolvahab; behrouz attarbashi moghadam; alireza ashraf; Mahmoud Jalili; Ahmadreza Baghestani (Shiraz University of Medical Sciences, 2017)
Background: Splinting is the most common conservative method of treating patients with mild and moderate Carpal Tunnel Syndrome (CTS). The aim of this study was to determine the effectiveness of the limited dynamic wrist splint on the symptoms, function, and strength of women with CTS. In this controlled trial study, the subjects wore a splint of a new design called the "limited dynamic wrist splint", which allowed the wrist motion in the range (between 15-degree flexion and 15-degree extension) that exerts minimum pressure on the median nerve and prevents extra pressure on the nerve by limiting the range of motions out of the allowed range. Methods: In this study, 24 women diagnosed with mild to moderate CTS were initially evaluated on the basis of the Boston questionnaire, the dexterity test of the Purdue pegboard, grip and pinch strength, distal sensory latency, and sensory nerve conduction velocity. The subjects were randomly divided into two groups, control and treatment. Both groups received routine rehabilitation treatment for six weeks. The treatment group received the limited dynamic wrist splint for about six to eight hours a day. After six weeks, the initial examinations were repeated. The SPSS-16, independent t, and paired t-tests were used for data analysis. Results: All the variables in the treatment and the control groups showed improvement. The function test of the Boston questionnaire, the Purdue pegboard test, and the pinch strength were significantly improved in the treatment group. The "severity of the symptoms" test of the Boston questionnaire and the pinch strength in the control group showed a statistically significant difference (P < 0.05). In a comparison of the two groups, the function test of the Boston questionnaire showed a significant difference. Conclusion: This study showed that the use of the limited dynamic wrist splint for about six weeks for six to eight hours a day could have a significant effect on the function, dexterity, and the pinch strength of patients with CTS. Not only can the patients receive treatment by this method, but they can also perform their daily activities to some extent.